Analysis development of a management accounting system management accounting of the JSC «National Company of Kazakhstan Railways». (Journal of Economic Research & Business Administration, 2016)
In a market economy for guidance of enterprise there was a necessity operatively to accept administrative decisions about logistical support of production resources, producing of competitive at the market products, mastering of new markets of sale, forming of own price politics and price strategies on different markets, the need of differentiated forms of realization and calculations. And also to foresee demand on the produced products in the future and to envisage events for his stimulation or reorientation of enterprise on the production of other types of products, or to diversify a product, develop directions of the alternative use of product. It requires information about suppliers, prices on resources, terms of transporting and payment, expenses, methods and technologies of production, about the market state of affairs, consumers, and development of NT, commodities and perspective necessities of people. In this article the system of administrative account is described on the example of JSC «National Company of Kazakhstan Railways»
Keywords: JSC «National Company of Kazakhstan Railways»; consolidated financial reporting; multimodal transport-logistic operator.